Mycophenolic acid is a drug with the potential to be repurposed for suppressing tumor growth and metastasis in osteosarcoma treatment - Jeerawan Klangjorhor (2020)
© 2019 UICC Our previous review of proteomics data showed that in osteosarcoma, some overexpressed proteins were targets of FDA-approved immunosuppressive and anti-arrhythmic drugs, including mycophenolate mofetil (MMF), ribavirin, leflunomide, azathioprine and digoxin. Here, these drugs were screened for growth inhibitory effects in human osteosarcoma cell lines, including MNNG/HOS, U2OS, SaOS-2, MG-63 and 143B cells. Only mycophenolic acid (MPA), an active metabolite of MMF, efficiently inhibited osteosarcoma cell growth with IC50 values of 0.46-7.3 μM; these values are in the therapeutic range for organ transplant patients. At a therapeutic dose (10 μM), MPA significantly inhibited colony formation, caused cell cycle arrest in the S phase, and induced apoptosis. Moreover, the in vitro invasion of osteosarcoma cells was reduced by MPA by inhibiting cell migration capability. The in vivo antitumor effect of MMF was determined in nude mice harboring 143B cell xenografts. Daily oral administration of 200 mg/kg/day MMF for 2 weeks significantly suppressed tumor growth in treated mice, achieving 57.4 ± 11.1% tumor growth inhibition. Compared with the vehicle group, the MMF group treated with 50–200 mg/kg/day for 3 weeks had a significant reduction in the number of lung metastatic nodules in a tail vein-lung metastasis model of 143B cells. MMF doses of 50, 100 and 200 mg/kg/day are approximately equivalent to the non-toxic doses of 0.25, 0.5 and 1 g/day in humans, respectively. These findings indicate that MPA/MMF can effectively control osteosarcoma tumor growth and metastasis. Thus, the potential to repurpose MPA/MMF for use in osteosarcoma chemotherapy is of great interest.